Lippincott illustrated review immunology - Doan, Thao (Lippincott's Illustrated Reviews series, 2013)
Offers presentation of essential immunology material, with: more than 300 full-color annotated illustrations, an outline format, chapter summaries, review questions, and case studies that link basic science to real-life clinical situations